Background pain in persons with chronic leg ulcers: An exploratory study of symptom characteristics and management. Issue 6 (13th December 2021) - Leren, Lena; Eide, Hilde; Johansen, Edda Aslaug; Jelnes, Rolf; Ljoså, Tone Marte
Abstract: This exploratory descriptive study aimed to describe characteristics and management of background pain related to chronic leg ulcers. A total of 121 participants were recruited from two wound care clinics using a consecutive sampling method. Data were obtained through screening interview, clinical examination, and questionnaires. The mean average background pain intensity was 4.5 (SD 2.56) (CI 95% 4.0‐5.0). Pain interfered mostly with general activity (mean 4.3), sleep (mean 4.1), and walking ability (mean 4.0) (0‐10 NRS). The most frequently reported descriptors of background pain were 'tender', 'stabbing', 'aching', and 'hot‐burning'. Most of the participants stated that the pain was intermittent. Less than 60% had analgesics prescribed specifically for ulcer related pain, and the respondents reported that pain management provided a mean pain relief of 45.9% (SD 33.9, range 0‐100). The findings indicate that ulcer related background pain is a significant problem that interferes with daily function, and that pain management in wound care is still inadequate.